A finite point algorithm for soil water-salt movement equation - Li, Fenhong; Hu, Gang; Abdeljawad, Thabet; Abbas, Muhammad (Advances in difference equations, 2021)
In this paper, we propose the meshless finite point method for solving a type of fluid flow problem. The moving least square function is combined with the collocation method to treat nonlinear one- and two-dimensional soil water-salt movement equations. An adaptive windward scheme is used to stabilize the numerical solution in regions with a large gradient change. Numerical examples with the comparison among the proposed method, finite element method and characteristic finite element method show that the meshless finite point method is more accurate and is used to eliminate the numerical oscillation phenomenon.